107 LESSONS LEARNED FOLLOWING COVID-19: PLANNING FOR FUTURE INFECTIOUS OUTBREAKS IN A RESIDENTIAL CARE SETTING. (25th October 2022) - Doyle, M; Louw, J; Corry, M
Abstract: Background: During the COVID-19 pandemic, maintaining resident and staff safety was a key priority. This study explored the experiences of the nursing team in a residential care facility for older adults and we report on the lessons learned for future infection control outbreaks. Methods: Following ethical approval, all members of the nursing team were invited to take part in a one-to-one virtual interview using Microsoft teams. Eleven interviews were conducted. The data were imported into NVIVO data management software and analysed using thematic analysis. Results: The findings highlight the importance of preparedness in terms of 'keeping the house in order' by having policy, guidelines and staff training up-to-date, so that they are easily amended to meet unexpected challenges. Having advanced care planning as part of routine care will ensure that the wishes of the residents are always respected. Keeping the channels of communication open by embracing technology and being technology ready emerged as key to relationship centred care. This was important for maintaining relationships between staff, residents, and family/caregivers, and was essential for resident and family well-being, particularly for residents with cognitive impairment. Conclusion: Scientific predictions indicate that the next pandemic may come sooner and be deadlier than COVID-19. Health care managers and staff need to be ready to ensure that quality care is maintained. In residential settings, disruption to routine care can be minimised by embedding aspects of care embraced during COVID-19, into routine practice. Advanced care planning, embracing technology, and ensuring staff training, policy and procedures are up-to-date will make sure they can be easily amended to address infection specific requirements and this, will enable health care workers respond to outbreaks efficiently.